Neuroprotective effects of human amniotic fluid stem cells‐derived secretome in an ischemia/reperfusion model. (7th October 2020) - Castelli, Vanessa; Antonucci, Ivana; d'Angelo, Michele; Tessitore, Alessandra; Zelli, Veronica; Benedetti, Elisabetta; Ferri, Claudio; Desideri, Giovambattista; Borlongan, Cesar; Stuppia, Liborio; Cimini, Annamaria
Abstract: Stem cells offer the basis for the promotion of robust new therapeutic approaches for a variety of human disorders. There are still many limitations to be overcome before clinical therapeutic application, including a better understanding of the mechanism by which stem cell therapies may lead to enhanced recovery. In vitro investigations are necessary to dissect the mechanisms involved and to support the potential development in stem cell‐based therapies. In spite of growing interest in human amniotic fluid stem cells, not much is known about the characteristics of their secretome and regarding the potential neuroprotective mechanism in different pathologies, including stroke. To get more insight on amniotic fluid cells therapeutic potential, signal transduction pathways activated by human amniotic fluid stem cells (hAFSCs)‐derived secretome in a stroke in vitro model (ischemia/reperfusion [I/R] model) were investigated by Western blot. Moreover, miRNA expression in the exosomal fraction of the conditioned medium was analyzed. hAFSCs‐derived secretome was able to activate pro‐survival and anti‐apoptotic pathways. MicroRNA analysis in the exosomal component revealed a panel of 16 overexpressed miRNAs involved in the regulation of coherent signaling pathways. In particular, the pathways of relevance in ischemia/reperfusion, such as neurotrophin signaling, and those related to neuroprotection and neuronal cell death, were analyzed. The results obtained strongly point toward the neuroprotective effects of the hAFSCs‐conditioned medium in the in vitro stroke model here analyzed. This can be achieved by the modulation and activation of pro‐survival processes, at least in part, due to the activity of secreted miRNAs. Abstract : Neuroprotective effects of human amniotic fluid stem cell‐secretome in an ischemia/reperfusion model.